Cross-sectional X-ray nano-diffraction and -reflectivity analysis of multilayered AlTiN–TiSiN thin films: Correlation between residual strain and bi-layer period. (October 2015) - Bartosik, M.; Arndt, M.; Rachbauer, R.; Krywka, C.; Koller, C.M.; Keckes, J.; Mayrhofer, P.H.
Graphical abstract: Abstract: A multi-layered AlTiN–TiSiN thin film with a bi-layer period of ∼6 nm is characterized by cross-sectional synchrotron X-ray nano-diffraction and -reflectivity using an X-ray beam size of 250 × 350 nm 2 . The complementary approach allows for simultaneous determining gradients of residual strains and bi-layer thickness along the film depth and demonstrates a correlation between them. The observed dependency allows for a residual strain gradient design in multilayered thin films.